Soil Organic Carbon Stocks in Mixed-Deciduous and Coniferous Forests in Austria - Jandl, Robert; Ledermann, Thomas; Kindermann, Georg; Weiss, Peter (Frontiers in Forests and Global Change, 2021)
Question We compared the soil organic carbon stock of the forests of an entire country. The objective of our research was establishing the differences between coniferous or deciduous forests with respect to soil carbon stocks. The question is relevant because coniferous forests are increasingly damaged by abiotic and biotic disturbances that are related to climate change. Deciduous forests are considered to be less vulnerable. Their soils are expected to be more persistent and reliable sinks for carbon dioxide. Methods Soil data are available from the Austrian Forest Soil Survey. Soils have been sampled on sites of the Austrian Forest Inventory. The data were stratified according to geology (carbonatic versus silicatic bedrock) and forest type (coniferous versus mixed-deciduous forest). These data were used to establish ground truth of soil carbon stocks. Further, we had simulation results of a coupled forest growth / soil carbon model. The scenarios built on the results of the Forest Inventory 2007/09 and reflect a business-as-usual forest management versus a climate-change adaptation scenario where forest managers replace coniferous with deciduous forests if site conditions permit it. The simulations were performed with the forest growth simulator CALDIS and the soil carbon model Yasso07. Results Based on the Austrian Forest Soil Survey carbon stocks of coniferous forests were consistently higher than in mixed-deciduous forests. This result applies both for the organic litter layer and the mineral soil to a depth of 50cm. The depth gradients of carbon were similar in both forest types. The simulation under a strong warming scenario showed an increase in the carbon stocks of soils when conifers are replaced by deciduous tree species. In the 150-year simulation the majority of forest sites will become suitable for deciduous forests. The build-up of a large soil organic carbon stock is driven by the stronger harvesting pressure on the remaining coniferous forests. Deciduous forests were in lesser demand and developed under a light forest intervention regime. However, towards the end of the century, when the temperature level is far above present levels, the soil organic carbon stocks declined. one one one one one